2023
DOI: 10.1038/s41467-023-42943-7
|View full text |Cite
|
Sign up to set email alerts
|

Accessible hotspots for single-protein SERS in DNA-origami assembled gold nanorod dimers with tip-to-tip alignment

Francis Schuknecht,
Karol Kołątaj,
Michael Steinberger
et al.

Abstract: The label-free identification of individual proteins from liquid samples by surface-enhanced Raman scattering (SERS) spectroscopy is a highly desirable goal in biomedical diagnostics. However, the small Raman scattering cross-section of most (bio-)molecules requires a means to strongly amplify their Raman signal for successful measurement, especially for single molecules. This amplification can be achieved in a plasmonic hotspot that forms between two adjacent gold nanospheres. However, the small (≈1−2 nm) gap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 71 publications
0
17
0
Order By: Relevance
“…Macromolecular proteins (streptavidin, thrombin) were incorporated via specific interaction using biotin or thrombin binding aptamer in the gap. This study showed the detection of macromolecular analytes with high specificity with millisecond integration time, which enabled single-molecule SERS measurements (Figure b) …”
Section: Development Of Sers-active Multimeric Structures Based On Dn...mentioning
confidence: 80%
See 2 more Smart Citations
“…Macromolecular proteins (streptavidin, thrombin) were incorporated via specific interaction using biotin or thrombin binding aptamer in the gap. This study showed the detection of macromolecular analytes with high specificity with millisecond integration time, which enabled single-molecule SERS measurements (Figure b) …”
Section: Development Of Sers-active Multimeric Structures Based On Dn...mentioning
confidence: 80%
“…This study showed the detection of macromolecular analytes with high specificity with millisecond integration time, which enabled single-molecule SERS measurements (Figure 5b). 149…”
Section: Development Of Sers-active Multimeric Structures Based On Dn...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, it remains extremely difficult to fully leverage the capabilities of plasmonic nanostructures for two main reasons: (1) the plasmonic nanostructures should be tightly assembled together at a predefined and well-controlled distance (just a few nanometers); and (2) the detected molecules must be precisely located in the hot spot region to benefit from the highest electromagnetic field enhancement. Remarkably, DNA origami-based plasmonic nanostructures are thought to hold promise for solving these two challenges owing to the addressability and programmability of DNA origami. First, this cutting-edge technology allows the precise assembly of plasmonic nanostructures with subnanometer spacings, controlled spatial orientations, and tunable stoichiometries. Second, unlike other methods based on random adsorption of molecules on SERS substrates, DNA origami-assembled plasmonic nanostructures provide sequence-defined binding sites that specifically place analyzed molecules in hotspots. Despite these elegant works, most DNA origami-based plasmonic nanostructures are designed for proof-of-concept demonstrations of single-molecule detection, in which Raman dyes are embedded within the origami pillar, as summarized in Table S1. That is, most DNA origami-based plasmonic structures are unable to respond to stimuli from specific chemical or biological molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Gold nanorods (AuNRs) exhibit versatile optical properties in the NIR-II window, rendering them invaluable for applications in plasmonic imaging, small molecule detection, and photothermal therapy. The high surface-to-volume ratio of AuNRs facilitates diverse surface functionalizations for applications in nanoprobes, sensors, and drug delivery, highlighting the significance of AuNR surface modification. However, challenges arise in DNA functionalization due to the cetyltrimethylammonium bromide (CTAB) bilayer formed during synthesis, hindering close contact with DNA and thus easy to induce aggregation of AuNRs.…”
mentioning
confidence: 99%